“Everyone Forgets That Knowledge is the Ultimate Weapon”: Information Seeking Practices in Buffy the Vampire Slayer - Hicks, Deborah; Whippey, Caroline (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper examines how information seeking practices are depicted in "Buffy the Vampire Slayer". As popular culture reflects culturally held assumptions, this paper examines what the depiction of information seeking practices in a popular television show can tell LIS researchers and practitioners about how such practices are culturally understood. Cette communication examine comment les pratiques de recherche d’information sont dépeintes dans « Buffy contre les vampires ». Puisque la culture populaire se veut le reflet de pratiques culturelles existantes, cette communication s’intéresse à ce que les pratiques de recherche d’information montrées dans une émission de télévision populaire peut apprendre aux chercheurs et aux praticiens en BSI sur la compréhension culturelle de la pratique.